Implementation of Village-Owned Enterprise Policy in Strengthening Local Economic Governance in Budo Village, North Minahasa Regency, Indonesia - Talumantak, Jerry H.; Mamonto, Fitri H.; Bulo, Laurens L. (International Journal of Information Technology and Education, 2026)
This article analyzes the implementation of Village-Owned Enterprise (BUMDes) policy in Budo Village, Wori District, North Minahasa Regency. The study is located within public administration, village governance, and policy implementation scholarship, and examines how formal regulation is translated into institutional practice, business management, community participation, and accountability. A qualitative descriptive approach was used through interviews, observation, and documentation involving village government actors, BUMDes managers, village consultative actors, community economic actors, and local stakeholders. The findings indicate that BUMDes implementation in Budo Village has produced important institutional and economic foundations, particularly through village deliberation, tourism-based business activity, community involvement in micro-enterprises, and recognition of mangrove tourism as a strategic local asset. However, implementation remains partially effective rather than fully institutionalized. Several weaknesses were identified: local regulation has not been fully harmonized with the newer national legal framework; financial reporting and asset documentation remain incomplete; business planning is still limited; supervision is more procedural than evidence-based; and human resource capacity is not yet sufficient for professional enterprise management. The determinant factors shaping implementation include institutional fit, regulatory clarity, supervision quality, human resource capacity, community participation, and the socio-economic capacity of village business actors. The article argues that BUMDes should be understood not merely as a village business unit, but as a hybrid public-economic institution that requires good governance, entrepreneurial capability, transparent accounting, and participatory accountability. The study contributes to policy implementation literature by showing that village enterprise success depends on the alignment between legal legitimacy, managerial capacity, local economic potential, community trust, and continuous institutional learning